Development of a portable assistive exoskeleton for human arm movements - Yongkun Zhao; Juzheng Mao; Masahiro Todoh (Electronics Letters, 2023)
Abstract Over the past two decades, the number of people with arm disabilities has dramatically increased. Many researchers have begun to concentrate on developing technologies to address this challenge. Exoskeleton is one of the most successful technologies out of these since it does not require medical staff to accompany the patients and can continually rehabilitate the patients until they regain the ability to move voluntarily. However, the majority of exoskeletons are anchored to the ground and individuals are unable to purchase one due to its high manufacturing costs. Furthermore, since this type of exoskeleton is anchored to the ground, patients must go to hospitals to get rehabilitation services. In this study, a portable assistive exoskeleton for human arm motions is designed to address this problem. This device can carry patients' arms to the desired position by adhering to a prescribed trajectory by medical specialists. The main parts of this exoskeleton are made of polylactic acid and produced using 3D printing technology. Therefore, the total manufacturing costs of the exoskeleton are not excessive and the weight of it is not high as well.